The (s)elective Mountain - Pierre Mercklé; Delphine Moraldo; Caroline Datchary; Benoît Tudoux (Revue de Géographie Alpine)
Are there social inequalities regarding access to the ‘nearby mountain’ - that is, mountain for day hikes or hikes lasting a few days with overnight stays in tents or refuges? Are they so strong that the hikers who meet on mountain paths and in and around mountain refuges share homogenous social profiles? Or does the ‘nearby mountain’ bring together people from different social backgrounds, with potentially antagonistic approaches and representations of the mountains? And what happens then? To answer these questions, the article draws on the results of a survey conducted between 2015 and 2017 mainly in and around two refuges accessible in a few hours from adjacent towns, one in the Pyrenees and the other in the Alps, using mixed methods (questionnaire, interview, observation, analysis of documentary corpus). The first two parts of the article explore the differentiation logics at work in the social space of recreational uses of the mountains, to show how they articulate in a complex way the tastes for performance (‘to sweat’), nature (‘to contemplate’) and sociability (‘to share’). The final section shows how the relations of domination that produce this particular social space are perceived through the tensions between users, whose discourses, structured by oppositions between ‘them’ and ‘us’, re-translate in the mountains social class relations developed in other social spheres and other spaces. Finally, the analysis shows that the domination of one type of user (belonging to the educated fractions of the privileged classes) and a distinctive type of use of the mountains (combining sporting asceticism, recharching one’s battery and cultivated sociability) means that the mountains are at once the site of opposition between socially differentiated uses, and the site of the maintenance of a dominant legitimate use that tends to overshadow the others.